2010
DOI: 10.1074/jbc.m109.076992
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like Factor 4 Promotes Differentiation by Transforming Growth Factor-β Receptor-mediated Smad and p38 MAPK Signaling in Vascular Smooth Muscle Cells

Abstract: KLF4 (Krüppel-like factor 4) has been implicated in vascular smooth muscle cell (VSMC) differentiation induced by transforming growth factor ␤ (TGF-␤). However, the role of KLF4 and mechanism of KLF4 actions in regulating TGF-␤ signaling in VSMCs remain unclear. In this study, we showed that TGF-␤1 inhibited cell cycle progression and induced differentiation in cultured rat VSMCs. This activity of TGF-␤1 was accompanied by up-regulation of KLF4, with concomitant increase in T␤RI (TGF-␤ type I receptor) express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
81
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 50 publications
2
81
0
Order By: Relevance
“…Although it has been demonstrated that KLF4 is regulated by various post-translational modifications, including phosphorylation, acetylation, and sumoylation, less is known if KLF4 is regulated by UPS (19,27,28,53). The present study has demonstrated that KLF4 is regulated by the proteolysis depending on ubiquitin.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Although it has been demonstrated that KLF4 is regulated by various post-translational modifications, including phosphorylation, acetylation, and sumoylation, less is known if KLF4 is regulated by UPS (19,27,28,53). The present study has demonstrated that KLF4 is regulated by the proteolysis depending on ubiquitin.…”
Section: Discussionmentioning
confidence: 50%
“…In addition to transcriptional regulation, KLF4 is also known to be subjected to multiple post-translational modifications, including acetylation (27), sumoylation (28,54), and phosphorylation (53). Our findings have provided another layer to our understanding of the KLF4 regulatory circuitry, which in addition could enhance our understanding about the pivotal role of KLF4 in stem cell biology and carcinogenesis.…”
Section: Discussionmentioning
confidence: 86%
“…Our discovery therefore adds HGF as a novel member of the few stimuli reported to regulate KLF4 expression , Feinberg et al, 2005Li et al, 2010;Liu et al, 2012). Additionally, it is noteworthy that we identified KLF4 as its own transcriptional activator (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…For instance, the role of KLF4 as an oncogene or a tumor suppressor largely depends on the functional status of p21 CIP1/WAF1 in the cells examined (Rowland et al, 2005). Additionally, KLF4 is responsible for TGF-b1-induced differentiation of vascular smooth muscle cells (Li et al, 2010), whereas it is a negative regulator of the prostatic EMT triggered by TGF-b1 (Liu et al, 2012). More strikingly, an opposite conclusion was described even in the same cell line MDA-MB-231 regarding the role of KLF4 in cell migration and invasion (Yori et al, 2010;Yu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the activation of MAPK induces the activation of transcriptional factor, krüppel like-factor, which acts as a transcriptional repressor of EC-SOD. 35,36) From these observations, we speculated that the reduction of EC-SOD might be not directly regulated by p38-MAPK, but, in part, by the activation and/or inactivation of transcriptional factors.…”
Section: Discussionmentioning
confidence: 99%